Increased reproductive success through parasitoid release at a range margin: Implications for range shifts induced by climate change. (26th January 2020) - Mackay, K. David; Gross, Caroline L.; Ryder, Darren S.
Abstract: Aim: We tested four hypotheses (a) that pioneer trees at distribution margins would receive fewer visits from pollinators and pollinator parasitoids than would trees in larger, established populations; (b) that predator release (lower rates of pollinator parasitism) would result in higher pollinator reproductive success; (c) that less competition among fewer pollinator foundresses would correlate with higher plant reproductive success and (d) that these effects would be greater at the plant species' expanding range margin. Location: The dry, western side of the Great Dividing Range in northern New South Wales, eastern Australia. Taxon: The rusty fig ( Ficus rubiginosa, Moraceae), its pollinator and the pollinator's parasitoids. Methods: We measured fruit (syconia) set per tree, seed set per syconium and fig‐wasp numbers (pollinators and non‐pollinators) per syconium in a total of 62 trees in 24 populations covering three distributional zones – the dry, western margin of the species' range, a more mesic, eastern margin at the species' altitudinal limit, and the zone between these two margins. These results were modelled against F. rubiginosa population size, the position of plant populations in relation to range margins, and climatic gradients of temperature and rainfall. Results: Lower rates of pollinator parasitism and less pollinator competition correlated with increased reproductive success in the pollinator and increased male fitness (in terms of pollen dispersal) and female fitness (in terms of seed per syconium) in isolated trees of F. rubiginosa, compared with trees in larger populations, particularly at F. rubiginosa's mesic, expanding range margin. Main Conclusions: Pollinator–predator release and pollinator–competition release can lead to increased pollinator and plant reproductive success in pioneer trees at range margins. This reinforces the need to understand biotic interactions underlying reproduction and dispersal at expanding range fronts if we are to understand and better predict the drivers and effects of climate‐change‐induced range shifts in plants and their pollinators.